BMI/A Is Associated to Blood Preasure Amoung 11 Class Student in MAN 4 Jakarta - Atmaji, Adella; Razaq, Asa Azkatu; Soekatri, Moesijanti Y.E. (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2024)
Overweight and central obese in Indonesia are increasing. The 2018 basic health research showed the prevalence of central obese at the age of 15 years was 31.0%. The prevalence of hypertension in Indonesia is 34.1%. The purpose of this study was to describe the body mass index according to age (BMI/A) and the ratio of waist-hip circumference (WHR) to blood pressure in class XI MAN 4 Jakarta. The study used a descriptive approach with a cross sectional design. The sampling method used a proportional systematic random sampling formula and the number of samples representing each department was determined by the stratified random sampling formula. The research was conducted on at MAN 4 Jakarta on 52 students of class XI for the academic year 2021/2022 aged 16-17 years. While the primary data collected were sample characteristics used interview , body mass index by age used microtoise tools and weight scale, waist- hip ratio, and blood pressure. Results: BMI/A most of the subjects had good nutritional status 63.5%, WHR most of the subjects were in the no-risk category 61.5%, most of the subjects had normal blood pressure 76.9%. There was no significant relationship between age, gender, family history of hypertension and waist-to-hip-ratio circumference (WHR) to blood pressure (p>0,05) and to a significant relationship between body mass index by age (BMI/A) to blood pressure (p<0,05). Conclusion: There is a normal blood pressure tendencies are common those who had a body mass index by age (BMI/A) are overweight or obese and waist-to-hip-ratio circumference (WHR) are at risk